2019
DOI: 10.1080/10255842.2019.1645837
|View full text |Cite
|
Sign up to set email alerts
|

Experimental platform to facilitate novel back brace development for the improvement of spine stability

Abstract: The spine or 'back' has many functions including supporting our body frame whilst facilitating movement, protecting the spinal cord and nerves and acting as a shock absorber. In certain instances, individuals may develop conditions that not only cause back pain but also may require additional support for the spine. Common movements such as twisting, standing and bending motions could exacerbate these conditions and intensify this pain. Back braces can be used in certain instances to constrain such motion as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies have shown that using a corset can reduce tension and support the back, thereby preventing and reducing back pain (Myung et al, 2018;van Duijvenbode et al, 2008). Many investigations on the design of spinal corsets have been conducted, but most of them are to fix spinal disorders (Ali et al, 2020;Cooper et al, 2019). Meanwhile, the design of the spinal girdle specifically for brick-making industrial workers and its effectiveness has not been explored much.…”
Section: Nursing Practicesmentioning
confidence: 99%
“…Several studies have shown that using a corset can reduce tension and support the back, thereby preventing and reducing back pain (Myung et al, 2018;van Duijvenbode et al, 2008). Many investigations on the design of spinal corsets have been conducted, but most of them are to fix spinal disorders (Ali et al, 2020;Cooper et al, 2019). Meanwhile, the design of the spinal girdle specifically for brick-making industrial workers and its effectiveness has not been explored much.…”
Section: Nursing Practicesmentioning
confidence: 99%
“…Therefore, when creating an interaction model, it may be necessary to identify own material parameters for the macroscopic behavior. A common approach for the abdomen is to assume one linear material parameter per body region and varying body postures (Périé et al, 2004;Cooper et al, 2019;Bonnaire et al, 2020), but among others, Huang and Zheng (2015) state that one parameter pure elasticity theory is not sufficient to meet the hyperelastic properties of soft tissue (van Loocke et al, 2006).…”
Section: Introductionmentioning
confidence: 99%